Rediscovering Recovery: Reconceptualizing Underlying Assumptions of Citizenship and Interrelated Notions of Care and Support. (23rd December 2012) - Vandekinderen, Caroline; Roets, Griet; Roose, Rudi; Van Hove, Geert
Abstract : Over the last few decades, research, policy, and practice in the field of mental health care and a complementary variety of social work and social service delivery have internationally concentrated on recovery as a promising concept. In this paper, a conceptual distinction is made between an individual approach and a social approach to recovery, and underlying assumptions of citizenship and interrelated notions and features of care and support are identified. It is argued that the conditionality of the individual approach to recovery refers to a conceptualization of citizenship as normative, based on the existence of a norm that operates in every domain of our society. We argue that these assumptions place a burden of self-governance on citizens with mental health problems and risk producing people with mental health problems as nonrecyclable citizens. The social approach to recovery embraces a different conceptualization of citizenship as relational and inclusive and embodies the myriad ways in which the belonging of people with mental health problems can be constructed in practice. As such, we hope to enable social services and professionals in the field to balance their role in the provision of care and support to service users with mental health problems.